2008
DOI: 10.1111/j.1755-0998.2008.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 14 polymorphic microsatellite markers for the blue and red shrimp, Aristeus antennatus (Crustacea, Decapoda)

Abstract: Eighteen microsatellite loci were isolated and characterized from the blue and red shrimp, Aristeus antennatus Risso 1816, a commercially exploited marine crustacean widely distributed throughout the Mediterranean Sea and in the eastern Atlantic. Polymorphism was assessed in a population (n = 20) from the southwestern Sardinian seas; 14 loci resulted polymorphic and showed from three to 13 alleles. The observed heterozygosity ranged from 0.2 to 0.85. These microsatellites will be potentially useful for the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…To avoid redundancy with previous reported microsatellites, a BLASTn search employing our entire database and using a significance threshold of e -values <10 −10 was performed against all published A. antennatus microsatellites ( Cannas et al , 2008 ). All contigs matching with already available A. antennatus microsatellites were not included in the further microsatellite development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid redundancy with previous reported microsatellites, a BLASTn search employing our entire database and using a significance threshold of e -values <10 −10 was performed against all published A. antennatus microsatellites ( Cannas et al , 2008 ). All contigs matching with already available A. antennatus microsatellites were not included in the further microsatellite development.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) diversity analyses of blue and red shrimp populations on a broad oceanographic scale have detected four genetic stocks: the Western Mediterranean Sea (WM), the Eastern Mediterranean Sea (EM), the Atlantic Ocean (AO) and the Indian Ocean (IO), but have failed to distinguish genetic divergence within the regional level ( Maggio et al , 2009 ; Roldán et al , 2009 ; Fernández et al , 2011 ; Marra et al , 2015 ). Surveys using a small number of microsatellites isolated using the FIASCO protocol ( Zane, Bargelloni & Patarnello , 2002 ) failed to distinguish any type of population structure within Italian fishing grounds ( Cannas et al , 2008 ; Cannas et al , 2012 ).…”
Section: Introductionmentioning
confidence: 96%
“…1988) with minor modifications, and resuspended in ddH 2 O. Individual genotypes were obtained using eight polymorphic microsatellite loci (Table 2) and following PCR conditions as in Cannas et al. (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Total DNA was extracted following the 'Salting Out' protocol (Miller et al 1988) with minor modifications, and resuspended in ddH 2 O. Individual genotypes were obtained using eight polymorphic microsatellite loci (Table 2) and following PCR conditions as in Cannas et al (2008). PCR products together with a ROX 400 size standard underwent capillary electrophoresis at BMR-Genomics Laboratories in Padova, Italy (http://www.bmr-genomics.com).…”
Section: Tissue Sampling Dna Extraction and Microsatellite Amplificamentioning
confidence: 99%
“…However, no allozyme divergence was found (Sardà et al 1998) and the differences were explained as being a response to hydrological and ecological characteristics of the 2 Mediterranean basins (Sarà 1985). Recently, new molecular markers (microsatellites, Cannas et al 2008; mitochondrial control region, Maggio et al 2009; 16S rDNA and cytochrome c oxidase subunit I [COI], Roldán et al 2009, Sardà et al 2010 were developed for the species, but until now their application has been limited to the Western and Central Mediterranean (Maggio et al 2009, Roldán et al 2009). In both studies, no genetic structuring was found within the study area.…”
Section: Introductionmentioning
confidence: 99%